Diamondback moth egg susceptibility to rainfall: effects of host plant and oviposition behavior. Issue 8 (22nd July 2019) - Rahman, Md Mahbubur; Zalucki, Myron P.; Furlong, Michael J.
Abstract: Oviposition patterns of the diamondback moth (DBM), Plutella xylostella L. (Lepidoptera: Plutellidae), differ between common cabbage ( Brassica oleracea L. var. capitata ) and Chinese cabbage ( Brassica rapa L. var. pekinensis ) (Brassicaceae) host plants. This study shows that the moth prefers to oviposit on adaxial rather than abaxial leaf surfaces and petioles of both host plants. More eggs were laid in leaf veins than on leaf laminas of both host plants, especially in Chinese cabbage, where 94.6% of eggs were laid in veins. On Chinese cabbage, very few eggs were laid in clusters (≥2 eggs), whereas on common cabbage approximately 30% of eggs were laid in groups of 2 or more eggs. Removal of wax from common cabbage leaves dramatically increased the number of eggs laid singly on the leaf lamina of treated plants, suggesting that leaf waxes affect how eggs are distributed by ovipositing DBM. Eggs were most susceptible to removal by rainfall from the plant surface immediately (<1 h) after oviposition and when close to hatching (>72h old) whereas they were least susceptible 24 h after oviposition. Eggs laid on common cabbage plants were more susceptible to simulated rainfall than eggs laid on Chinese cabbage plants. On common cabbage plants, egg susceptibility to rainfall on different plant parts ranked adaxial leaf surfaces>petioles = abaxial leaf surfaces>stem, but there was no difference in egg susceptibility to rainfall on the various plant parts of Chinese cabbage. Furthermore, on common cabbage plants, eggs laid on both adaxial and abaxial leaf surfaces were afforded significant protection from the effects of rainfall by leaves higher in the plant canopy. On common cabbage plants, oviposition patterns reduce the potential impact of rainfall on eggs, possibly reducing the effect of this important abiotic mortality factor in the field. Abstract : Rainfall events can be a major source of mortality of eggs of diamondback moth, Plutella xylostella (Lepidoptera: Plutellidae). The effects of simulated rain vary considerably between host plant species (common cabbage, Brassica oleracea, and Chinese cabbage, Brassica rapa ) (Brassicaceae) and between oviposition sites within plants (adaxial and abaxial leaf surfaces, petioles, or stem).